Promosi Kesehatan “Sadari” Menggunakan Instagram pada Mahasiswi Non Kesehatan Universitas Andalas - Ayulia Fardila Sari ZA; Nengsih Purnama Sari; Nabila Nabila (Media Kesehatan Masyarakat Indonesia, 2019)
The incidence of breast cancer in West Sumatra Province ranks third out of 34 provinces in Indonesia,with an estimated number of 2,285 breast cancer patients. Based on the initial study, 18 out of 30 female studentslearned about the term Breast Self Examination (BSE), but 14 people have never done BSE. Health promotioninnovation efforts involving the use of social media Instagram is needed to improve knowledge, attitudes, andperceptions of the usefulness of technology in reducing the incidence of breast cancer. The purpose of this study isto measure the effect of BSE health promotion through Instagram social media on increasing knowledge, attitudes,and perceptions of the usefulness of technology in Andalas University students. The type of research is quasiexperiment with a non equivalent pretest post test design approach. The sample in this research are non medicalstudent of Andalas University amounted to 61 people. The result of the research, there was differences in theaverage score of knowledge, attitudes, and perceptions of the usefulness of the respondents technology before andafter BSE health promotion using Instagram social media (p value <0.05) and Instagram can provide convenienceto users in disseminating health information visually as widely as possible with an attractive appearance.